Hezychia bramą do zjednoczenia z Bogiem według traktatu Drabina raju św. Jana Klimaka - Wójtowicz, Marcin (Poznańskie Studia Teologiczne, 2022)
John Sinaites devoted the last part of his treatise The Ladder of Divine Ascent to the discussion of a breakthrough moment in asceticism, which opens the way into a mystical relationship with God. What is indinspensable to achieve it are the four gifts that a monk receives from God: hesychia, prayer, dispassion (apatheia) and love. Although each of them is vital in the process of unification, in Climacus’s opinion the most important of them is hesychia, understood as a gateway to union with God, a bridge between the intertwining spheres of asceticism and mysticism.